Perkembangan Digital Zakat di Indonesia : Analisa Bibliometrik - Nadia Meirani; Rizka Estisia Pratiwi (Universitas Islam Bandung, 2023)
People in Indonesia are already involved with the internet and involve it in their lives. Referring to these conditions, it provides an opportunity for Financial Technology to develop in Indonesia, especially Sharia FinTech, because the majority of the population is Muslim. One of the implementations is digital zakat payments. However, there are still pros and cons because the implementation of digital zakat must follow sharia principles. Some say that digital zakat makes it easy for muzakki because they can pay zakat wherever and whenever and according to the current lifestyle of society. Indonesia, which is dominated by Millennials at a productive age, can be the right target for implementing digital zakat. The development of digital zakat in Indonesia is quite good because there are currently many digital zakat platforms so that people can easily choose. The method used in this study is bibliometric analysis using vosviewer, with the aim of seeing how far digital zakat has developed in Indonesia.